Aprendizagem significativa de conceitos de física integrado a participação na mostra brasileira de foguetes - Angelo, Luan Cícero da Silva (2021)
This work is the result of the experience we had in participating in the Brazilian Rocket Launch Exhibition (MOBFOG) and the Jornada Cearense de Rocket (JCF), using as a teaching strategy for some content, workshops for building PET bottle rockets and bases launches. The work was carried out with elementary and high school students seeking to bring them closer to the competences and skills established by the National Common Curricular Base (BNCC) for the Earth and Universe axis. The contents related to Newton's Laws, center of mass, center of pressure, physical states of matter and their properties were discussed and addressed. In order to collect data that would help us to know if the strategy resulted in learning, we used qualitative activities through forms, questionnaires, interviews and other notes. The execution of the scripts of the didactic sequences allowed a differentiated learning through investigative activities that favored the interdisciplinarity and the contextualization of the contents.